A High Performing Zn‐Ion Battery Cathode Enabled by In Situ Transformation of V2O5 Atomic Layers. Issue 39 (6th August 2020) - Lu, Yanying; Zhu, Tianyu; van den Bergh, Wessel; Stefik, Morgan; Huang, Kevin
Abstract: Developing high capacity and stable cathodes is a key to successful commercialization of aqueous Zn‐ion batteries (ZIBs). Pure layered V2 O5 has a high theoretical capacity (585 mAh g −1 ), but it suffers severe capacity decay. Pre‐inserting cations into V2 O5 can substantially stabilize the performance, but at an expense of lowered capacity. Here we show that an atomic layer deposition derived V2 O5 can be an excellent ZIB cathode with high capacity and exceptional cycle stability at once. We report a rapid in situ on‐site transformation of V2 O5 atomic layers into Zn3 V2 O7 (OH)2 ⋅2 H2 O (ZVO) nanoflake clusters, also a known Zn‐ion and proton intercalatable material. High concentration of reactive sites, strong bonding to the conductive substrate, nanosized thickness and binder‐free composition facilitate ionic transport and promote the best utilization of the active material. We also provide new insights into the V2 O5 ‐dissolution mechanisms for different Zn‐salt aqueous electrolytes and their implications to the cycle stability. Abstract : Atomic layer deposition derived V2 O5 (ALD‐V2 O5 ) as a high‐capacity and stable ZIB cathode is reported. Direct and compelling evidence shows that ALD‐V2 O5 undergoes an in situ on‐site transformation into nanoscaled Zn3 V2 O7 (OH)2 ⋅2 H2 O (ZVO) and the latter is largely responsible for the excellent electrochemical performance. We also offer our new understanding on the capacity degradation mechanisms.